2006
DOI: 10.1186/1741-7015-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Alternating ibuprofen and acetaminophen in the treatment of febrile children: a pilot study [ISRCTN30487061]

Abstract: BackgroundAlternating ibuprofen and acetaminophen for the treatment of febrile children is a prevalent practice among physicians and parents, despite the lack of evidence on effectiveness or safety. This randomized, double-blind and placebo-controlled clinical trial aims at comparing the antipyretic effectiveness and safety of a single administration of alternating ibuprofen and acetaminophen doses to that of ibuprofen mono-therapy in febrile children.MethodsSeventy febrile children were randomly allocated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 13 publications
1
44
0
4
Order By: Relevance
“…[71][72][73][74][75] Initially, changes in temperature were similar for all groups in these studies, regardless of therapy. However, 4 or more hours after the initiation of treatment, lower temperature was consistently observed in the combinationtreatment groups.…”
Section: Alternating or Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…[71][72][73][74][75] Initially, changes in temperature were similar for all groups in these studies, regardless of therapy. However, 4 or more hours after the initiation of treatment, lower temperature was consistently observed in the combinationtreatment groups.…”
Section: Alternating or Combination Therapymentioning
confidence: 99%
“…For example, 6 and 8 hours after the initiation of the study, a greater percentage of children were afebrile in the combination group (83% and 81%, respectively) compared with those in the group that received ibuprofen alone (58% and 35%, respectively). 71 Only 1 study 72 evaluated issues related to stress and comfort and found lower stress scores and less time missed from child care in the combination-treatment group. Another study 73 showed a trend toward a normalization of fever-related symptoms by 24 and 48 hours after institution of therapy, but these trends disappeared by day 5.…”
Section: Alternating or Combination Therapymentioning
confidence: 99%
“…The Israeli study 50 design appears to be difficult to interpret as half the children received both medicines in the first 24 hours and parents determined the timing of thermometry and distress scores. The Lebanese study 51 was probably accepted for publication as a pilot because of the large, statistically and clinically significant treatment effects in favour of combined treatment up to 4 hours post paracetamol dosing, but may be an example of publication bias. The American study found statistically but probably clinically unimportant temperature differences at 4 and 5 but not 6 hours when ibuprofen was added to paracetamol after 3 hours.…”
Section: Summary Of Limitations Of Previous Researchmentioning
confidence: 99%
“…51 All had rectal temperatures ≥ 38.8°C and the study aimed to assess the benefits of adding paracetamol (15 mg/ kg) or placebo 4 hours after a baseline dose of ibuprofen (10 mg/kg). The authors found that more children in the active group than in the placebo group (83% versus 58% respectively) were afebrile at 6 hours [number needed to treat (NNT) = 4], and that these effects persisted for up to 8 hours.…”
Section: Evidence For Using Paracetamol and Ibuprofen Togethermentioning
confidence: 99%
See 1 more Smart Citation